Hydrocarbon Pollution: Effects on Living Organisms, Remediation of Contaminated Environments, and Effects of Heavy Metals Co-Contamination on Bioremediation - Abha, Shukla; Singh, Cameotra Swaranjit (IntechOpen, 2012)
None